Development of a risk assessment tool for Japanese sex offenders: The Japanese Static‐99 - Takayuki Harada; Kazutaka Nomura; Hironori Shimada; Norito Kawakami (Wiley, 2023)
Abstract In Japan, sexual offending, especially paraphilic sexual offending, has become a major problem, and approximately 3000 people are arrested for frotteuristic and voyeuristic behavior each year. Considering the repetitive nature of such behaviors, determining the recidivism risk is imperative. Globally, Static‐99 is one of the most widely used actuarial risk assessment tools to predict recidivism among sex offenders. However, sexual offending is largely influenced by social and cultural backgrounds, and whether risk factors identified in the West are applicable to other countries is unknown. Therefore, we developed a Japanese version of the Static‐99 and examined its reliability and validity with 167 Japanese paraphilic sex offenders. The results showed good internal consistency (Cronbach's alpha coefficient = 0.88) and predictive accuracy (area under the curve = 0.76). The results indicate that the Japanese Static‐99 can be used with Japanese sex offenders. Moreover, risk factors identified in the Western context are applicable to Japanese sex offenders despite the different nature and manifestations of their offending.